2018
DOI: 10.1002/jmv.25266
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency testing for the detection of Middle East respiratory syndrome coronavirus demonstrates global capacity to detect Middle East respiratory syndrome coronavirus

Abstract: The first reported case of Middle East respiratory syndrome coronavirus (MERS-CoV) infection was identified in Saudi Arabia in September 2012, since which time there have been over 2000 laboratory-confirmed cases, including 750 deaths in 27 countries. Nucleic acid testing (NAT) is the preferred method for the detection of MERS-CoV. A single round of a Proficiency Testing Program (PTP) was used to assess the capability of laboratories globally to accurately detect the presence of MERS-CoV using NAT. A panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…130 These findings also need to be couched in the context of potential test fallibility for a variety of reasons. 131 From nasopharyngeal samples, both viral RNA and culture-viable MERS-CoV can be found in patients past 14 days. 124,132 Viral RNA can be detected for up to 27 to 47 days (average 14 days) in stool samples.…”
Section: Mers-cov and Enteric Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…130 These findings also need to be couched in the context of potential test fallibility for a variety of reasons. 131 From nasopharyngeal samples, both viral RNA and culture-viable MERS-CoV can be found in patients past 14 days. 124,132 Viral RNA can be detected for up to 27 to 47 days (average 14 days) in stool samples.…”
Section: Mers-cov and Enteric Diseasementioning
confidence: 99%
“…One review proposed that some 12% to 25% of identified MERS‐CoV infections are asymptomatic 130 . These findings also need to be couched in the context of potential test fallibility for a variety of reasons 131 …”
Section: Human Coronaviruses As Enteric Pathogensmentioning
confidence: 99%
“…In particular, the development and validation process for new diagnostics could be accelerated if well-characterised specimens and reference standards could be more easily obtained. EQA can be useful for evaluation of test performance, as shown with evaluations of both inhouse and commercial assays for MERS-CoV,111–113 and more recently a global proficiency testing programme used to assess laboratory detection of MERS-CoV 114. Even after validation, a substantial amount of reference material is required for quality control; often manufacturers must develop their own calibration standards to maintain supply and to control lot-to-lot variability.…”
Section: Challenges For Mers-cov Diagnosticsmentioning
confidence: 99%
“…Therefore, on the one hand, it is necessary to strengthen the training and management of personnel within the laboratory. On the other hand, it is necessary to deepen the supervision and construction of the quality system comprehensively to cope with the outbreak of a series of infectious diseases such as SARS and MERS ( Fig.6 ) [27] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%